Employee Performance Based on Workload and Job Stress at the Grand Cempaka Resort & Convention Hotel Bogor - Endang Silaningsih; Rohmat; Yulianingsih (MultiTech Publisher, 2024)
The purpose of this study is to ascertain how the Grand Cempaka Resort & Convention Hotel Bogor's workforce is affected, both partially and simultaneously, by work stress and workload. The Grand Cempaka Hotel's employees made up the study's population. Using the purposive sampling method, 60 respondents served as the sample size. Descriptive and verification methods were utilized in data analysis, with IBM SPSS version 25.00 being used. The findings of the study demonstrate that workload and work stress both have a negative and considerable impact on employee performance.